Pengaruh Perhatian Orang Tua dan Pembelajaran Jarah Jauh terhadap Kesadaran Berakhlak Mulia Peserta Didik - Muhammad Qowiyul Aziz; A. Mufrod Teguh Mulyo (Program Pascasarjana UNU Surakarta, 2022)
Parental attention is one of the essential factors in supporting the growth and development of children, especially in the world of education. This study aims to analyze the effect of parental attention and distance learning on the awareness of the noble character of the VIII grade students of MTsN Boyolali academic year 2020/2021. This quantitative research was carried out in May – July 2021. The population was 211 people, and the sample, according to Krejcie and Morgan's table, was 136 people or 64.45%. The sampling technique used stratified simple random sampling. Collect data using questionnaires, interviews, and observations. Data analysis used descriptive analysis, Product Moment correlation, regression, t-test, F test, and R2 test. The results showed parental attention's influence on the awareness of students' noble character with tcount 7.941 > ttable 1.97. The effect of distance learning on the understanding of noble character with tcount 6.898 > ttable 1.97. The influence of parental attention and distance learning on the awareness of the noble character of class VIII MTsN 10 Boyolali students in the 2020/2021 academic year can be seen from the Fcount of 50.980 and the significance value of 0.000 so that the p-value (0.000) <0.05. The contribution of parental attention and distance learning to awareness of noble character is 43.4%, while the remaining 56.6% indicates the magnitude of the influence of other variables outside the research model.